Responsibility of Banks in Preventing Name Abuse in Credit Applications - Firmanto, Ruddy; Hardyansah, Rommy; Darmawan, Didit (Bulletin of Science, Technology and Society, 2024)
The phenomenon of name lending agreements in banking credit in Indonesia is increasingly common, where an individual uses the name of a third party to obtain a credit facility without the consent of the party whose name is lended. This practice poses significant legal and financial risks, especially for the party whose name is used, who may be trapped in credit repayment obligations they did not make. Statute 1873 of the Civil Code of Indonesia provides that such agreements are deemed null and void in the absence of the consent of the named lender. Nonetheless, the implementation of legal protection for the injured party often faces obstacles, such as the lack of formal evidence and legal awareness of the party whose name is used. This study aims to analyze the application of Statute 1873 of the Civil Code of Indonesia in protecting the rights of the party whose name is used in a name lending agreement as well as explore the role of banks in preventing the practice. The results are expected to contribute to policy development and better legal protection for customers.